Preparation of Ta2O5 nanoparticles by using cathode glow discharge electrolysis - Quan-Fang Lu; Juan-Long Li; Jie Yu; Li-Juan Cui; Bo Wang; Xiao-Juan Ma; Yan Feng (Materials Research Express, 2021)
Tantalum pentoxide nanoparticles (Ta _2 O _5 NPs) were fabricated by cathode glow discharge electrolysis (CGDE) generated between a needle-like platinum wire cathode and a tantalum foil anode in 6 g L ^−1 Na _2 SO _4 electrolyte solution containing 5 ml hydrofluoric acid (HF) and 0.075 g cetyltrimethyl ammonium bromide (CTAB). The chemical structure, composition and morphology of the obtained powder were analyzed by using XRD, FT-IR, SEM/EDS, XPS and UV–vis DRS. The results found that Ta _2 O _5 NPs with orthorhombic structure and wide band gap (3.6 eV) are successfully fabricated at 500 V discharge voltage in about 3 h. CTAB as a stabilizing agent can reduce the agglomeration due to forming CTA ^+ and attaching the surface of the synthetic products. A possible preparation mechanism of Ta _2 O _5 NPs is proposed. Firstly, the tantalum foil anode is oxidized to form a compact Ta _2 O _5 layer. Then, Ta _2 O _5 surface is etched to form soluble [TaF _7 ] ^2− complexes in the presence of HF. After that, soluble [TaF _7 ] ^2− complexes can react with H _2 O to form Ta(OH) _5 . Finally, Ta(OH) _5 is further converted to Ta _2 O _5 from plasma-liquid interface into solution.